2017
DOI: 10.1016/j.jwpe.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effluent quality of an industrial wastewater treatment plant by way of optical monitoring

Abstract: Wastewater samples taken from the aeration tank of a full-scale activated sludge plant were analyzed using an automatic optical monitoring device. Five variable selection methods were utilized to find the optimal subsets of input variables to develop predictive models for the important parameters of the wastewater treatment process efficiency and the quality of the effluent, including suspended solids, biochemical oxygen demand, chemical oxygen demand, total nitrogen and total phosphorus. The dependencies betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Many core raw water quality parameters were relevant as expected, which are defined, for example, BOD Raw being the core parameter for the BOD Treated model. The correlations were weak for the TSS Treated model, as the highest correlation was observed to be 0.32 with TS Raw and the lowest was 0.08 with process type, which were similar to the relationships shown in Mjalli et al [29] and Tomperi et al [7] between water quality parameters. These correlations were used as the basis for selecting the different input parameters for the studied models.…”
Section: Tsssupporting
confidence: 82%
See 2 more Smart Citations
“…Many core raw water quality parameters were relevant as expected, which are defined, for example, BOD Raw being the core parameter for the BOD Treated model. The correlations were weak for the TSS Treated model, as the highest correlation was observed to be 0.32 with TS Raw and the lowest was 0.08 with process type, which were similar to the relationships shown in Mjalli et al [29] and Tomperi et al [7] between water quality parameters. These correlations were used as the basis for selecting the different input parameters for the studied models.…”
Section: Tsssupporting
confidence: 82%
“…More importantly, it shows which input parameters have a good relationship with the dependent variable. Tomperi et al [7] also used linear correlation analysis to identify variables that impact each other, similarly, BOD and COD have the highest correlation, while other parameters did not show similar results. This is due to the wide variety of wash-waters/wastewater explored in this study compared to the single source, pulp, and paper mill in studies by Tomperi et al [7].…”
Section: Tssmentioning
confidence: 99%
See 1 more Smart Citation
“…SVI has been use widely to test sludge settleability in both laboratory scale and pilot plant scale studies [35]. The settleability of activated sludge systems can also be monitored and controlled through microscopic observation [13,36]. Quantitative image analysis is a promising technique which has been used to study different problems in activated sludge systems [2,13,37,38].…”
Section: Morphological Study and Image Analysis Procedures For The Sludgementioning
confidence: 99%
“…The importance of using a plan for online measurements verification and for online sensor maintenance was discussed by Smith (2017). Tomperi et al (2017) demonstrated that the models based solely on optical monitoring variables were able to be used to predict the level of the effluent quality parameters hours before the traditional sampling and analyses. Optical monitoring variables were deemed a potential tool to be used to maintain stable process control.…”
Section: Monitoring and Instrumentationmentioning
confidence: 99%